Answer:
The answer to your question is (x + 3)
Step-by-step explanation:
![\frac{5x + 5}{x} \frac{x^{3}+ 3x^{2}}{x^{2} - 1} \frac{x - 1}{5x}](https://tex.z-dn.net/?f=%5Cfrac%7B5x%20%2B%205%7D%7Bx%7D%20%5Cfrac%7Bx%5E%7B3%7D%2B%203x%5E%7B2%7D%7D%7Bx%5E%7B2%7D%20-%201%7D%20%5Cfrac%7Bx%20-%201%7D%7B5x%7D)
Factor the expression
![\frac{5(x + 1)}{x} \frac{x^{2}(x + 3)}{(x - 1)(x + 1)} \frac{x - 1}{5x}](https://tex.z-dn.net/?f=%5Cfrac%7B5%28x%20%2B%201%29%7D%7Bx%7D%20%5Cfrac%7Bx%5E%7B2%7D%28x%20%2B%203%29%7D%7B%28x%20-%201%29%28x%20%2B%201%29%7D%20%5Cfrac%7Bx%20-%201%7D%7B5x%7D)
Simplify
Cancel 5 because is in both numerator and denominator
Cancel (x + 1) because is in both numerator and denominator
Cancel (x - 1) because is in both numerator and denominator
Cancel x² because is in both numerator and denominator
After simplifying, the result is (x + 3)
Answer:f(x)= 3*1/k
8=3*1/k
K=3/8
When x=2
f(x)=2*3/8
f(x)=3/4
Step-by-step explanation:
Answer:
the answer is two
Step-by-step explanation: